2021
DOI: 10.3390/ijerph18063112
|View full text |Cite
|
Sign up to set email alerts
|

Provision of Care to the People with HIV: Voices of Professional Nurses in the Public Hospitals of Limpopo Province, South Africa

Abstract: The battle against the Human Immunodeficiency Virus (HIV) and Acquired Immunodeficiency Syndrome (AIDS) epidemic are still raging in South Africa (SA) despite all the preventive strategies implemented via the five-year strategic plan (2011–2015). The intensity of the AIDS pandemic in SA creates additional challenges for the health workers as they have to deal with an increasing number of people who suffer from this disease. Professional nurses are a critical part of the workforce. The qualitative, explorative,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 27 publications
(29 reference statements)
0
4
0
Order By: Relevance
“…This means that some of the participants might even have been infected with HIV, carrying the physical effects of living with HIV and its corresponding opportunistic infections. The risk of contracting HIV while working with patients living with HIV is a reality which has also been documented by Moshidi et al [ 13 ], where participants mentioned that they accidently could have touched patients' body fluids, while delivering invasive or noninvasive medical intervention in an emergency. They thought that they would be safe from HIV exposure if they took precautions when in direct contact with the patient.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…This means that some of the participants might even have been infected with HIV, carrying the physical effects of living with HIV and its corresponding opportunistic infections. The risk of contracting HIV while working with patients living with HIV is a reality which has also been documented by Moshidi et al [ 13 ], where participants mentioned that they accidently could have touched patients' body fluids, while delivering invasive or noninvasive medical intervention in an emergency. They thought that they would be safe from HIV exposure if they took precautions when in direct contact with the patient.…”
Section: Discussionmentioning
confidence: 77%
“…The stigma of and discrimination against people living with HIV do not end only in general wards but also extend to special nursing units such as the theatre. Theatre nurses view their environment as stressful and not conducive to providing quality care to patients living with HIV [ 13 ]. Studies have indicated the reluctance of nurses to scrub for a patient living with HIV.…”
Section: Introductionmentioning
confidence: 99%
“…This contention seems to fit the thoughts of Dilu et al (2017), who argue that low government support creates several issues such as lack of skilled employees, heavy workload, staff turnover, high absenteeism and poor commitment in the health sector. Interestingly, these issues are part of the major reasons why HRIS has not been able to prove its efficiency in the health sector (Maruru, 2014;Moshidi, Malema, Muthelo, & Mothiba, 2021).…”
Section: Government Support For Effective Hris Adoption In the Health Sectormentioning
confidence: 99%
“…Kigoma region decided to comprehensively accelerate the HIV interventions, including providing frontline healthcare providers with skills and knowledge, provision of essential equipment, and other infrastructure per National AIDS control guidelines to institutional capacity to provide HIV and AIDS care to PLHIV [ 10 ]. Afterward, the region assessed the HIV and AIDS service delivery.…”
Section: Introductionmentioning
confidence: 99%